Retrofit Analysis of Florida Beam-and-Post Reinforced Concrete Bridge Barriers - J.W. Wekezer; I. Kreja; M. Issa (Engineering Transactions, 2015)
The major objective of the study was to evaluate crashworthiness of the existing. Florida Beam-and-Post reinforced concrete bridge barriers. These barriers were first installed thirty years ago, they are still popular, and represent a significant investment in transportation infrastructure of the State. The major emphasis of the paper is focused on utilization of computational mechanics to improve safety of the existing reinforced concrete bridge rails. It presents results of analytical efforts to simulate crash impacts between a pickup truck and the Florida Beam-and-Post barrier. Computer .calculations were performed using LS-DYNA, explicit, dynamic, 3-D finite element code. Finite element models of a 2000P Chevrolet pickup truck and the model of the bridge barrier were used to simulate test 3-11 per NCHRP Report 350. Computer simulations revealed severe snagging problems and provided input for a better understanding of the barrier response. Specific recommendations for a retrofit of the existing Florida Beam-and-Post barriers were provided. These recommendations include guidelines for new, proposed, safe reinforced concrete bridge barriers for consideration by transportation engineers.